Análisis del desempeño del recurso humano y su incidencia en la calidad del servicio brindado a los socios de la COAC. "C.C.C.B. LTDA" - Vera Solórzano, Lourdes Viviana (2010)
The main objective of the present investigation was to analyze the acting of the human resource of the Cámara de Comercio “Cooperative of Saving and Credit of Bolivar” city, where a number of customers were interviewed with the purpose of diagnosing the developing of each employee in its functions to improve the quality of the service offered to the customers. The methodological aspect was characterizes for a descriptive type, with a field and documental stage; the techniques used were based in the direct survey to 66 customers. The questionnaire structured is constituted with ten questions and the direct interview to the human resource with seven questions the same ones that validated the instruments used in the investigation, the results were tabulated and analyzed in qualitative and quantitatively way, the information was classified according to their nature to later way to analyze the result obtained and like this obtain the recommendations and conclusions for the improvement in the service to the collective that they will serve as tool of the taking of decisions to future. At the last point, It was elaborated a tab of the evaluation of the Acting of the human resource according to their functions that allows to offer a better service in order to maintain the personnel’s constant control, the same one that will be applied once a year by the manager of the Cooperative and this will serve like an instrument for the improvement, because nowadays the financial institution are looking for the survival between the social environment and this way to respond to the impact of competition on the market. A aspect very important in all organization is the human resource, because through this the organizational objectives can be fulfilled and through this investigation it determined that the human resource that works in the Cooperative has a level of acceptable academic preparation and they have taken to increased the number of customers, the same ones are feeling satisfied with the acting of the personnel’s attentions.